18=3m-m

Simple and best practice solution for 18=3m-m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18=3m-m equation:



18=3m-m
We move all terms to the left:
18-(3m-m)=0
We add all the numbers together, and all the variables
-(+2m)+18=0
We get rid of parentheses
-2m+18=0
We move all terms containing m to the left, all other terms to the right
-2m=-18
m=-18/-2
m=+9

See similar equations:

| 1/5(2a-5)-4=1/2(a+4)=7/10 | | 3(x+5)=6-3(2x+4) | | 7y-8-6y=+1 | | -8.5x+0.51=-6.29 | | 28=10x-3x | | X-5×x=84 | | 3(5x+6)+4(6x+3)+6=39x+37 | | e/4-3=3 | | 2+y/2+4y/5=y-2/3 | | n/6+12=-8 | | 2m-25=8m+13 | | 9=q–4 | | 4z7+7=-7 | | 89=8x | | 7q-3=18 | | 12(2k+11=12(2k+12) | | 60^s+80s=-25 | | 3/4b-4=-7/8b+1 | | 46-5a=10-9a | | (4m+2)(3m-2)=0 | | -11(d+7)=11 | | -11b=7+40 | | 16)8(11-x)=16 | | x+17=22–22 | | 3^2x=6651 | | 24x-24=24x+24 | | 15)7(2+x)=35 | | 1/6x+1/8=27/8 | | 9-2x-(2x^-1/2)=0 | | 14)9(x+9)=90 | | 16=10-4(5-5w) | | 21y-11=18y+1 |

Equations solver categories